8-Methoxy-4-(4-methoxyphenyl)quinoline - Ligia Llovera; Teresa González; Pavel Anzenbacher Jr; Simón E. López (Acta Crystallographica Section E, 2010)
In the title compound, C17H15NO2, the dihedral angle between the quinoline and benzene ring systems is 62.17 (1)°. In the crystal, zigzag chains propagating in c are linked by C—H...O hydrogen bonds, and weak C—H...π interactions link the chains.